Recent Advances in the Role of Nuclear Factor Erythroid-2-Related Factor 2 in Spinal Cord Injury: Regulatory Mechanisms and Therapeutic Options - Jiang, Tianqi; He, Yongxiong (Frontiers in Aging Neuroscience, 2022)
Nuclear erythroid 2-related factor 2 (Nrf2) is a pleiotropic transcription factor, and it has been documented that it can induce defense mechanisms both oxidative stress and inflammatory injury. At present, more and more evidences show that the Nrf2 signaling pathway is a key pharmacological target for the treatment of spinal cord injury (SCI), and activating the Nrf2 signaling pathway can effectively treat the inflammatory injury and oxidative stress after SCI. This article describes the biological studies of the Nrf2 pathway and the mechanisms involved in Nrf2-related oxidative stress and inflammatory responses. At the same time, several identified drugs that can enhance Nrf2 activation and Nrf2-dependent gene expression for the treatment of SCI are reviewed, as well as some therapeutic strategies to treat other aspects of SCI by modulating the Nrf2 pathway. It will provide new ideas and directions for the treatment of SCI.